2019
DOI: 10.1016/j.cub.2019.06.072
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Barriers Disrupt Grid-like Representations in Humans during Navigation

Abstract: Highlights d Human participants engaged in a non-memory-based VR foraging task d Grid-cell-like representations are observed in open-field environments d Grid-cell-like representations are disrupted in environments with hairpin barriers d Entorhinal signals develop a 4-fold periodicity in barrier environments Authors Qiliang He, Thackery I. Brown

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 29 publications
7
30
1
Order By: Relevance
“…Consistently with rodent data 63 , it has recently been demonstrated that physical restrictions of navigation possibilities in the environment (e.g. by physical spatial constraints) disrupt the hexadirectional GCLR modulation in humans 64 . By such restrictions, firing fields of grid cells do not tile in typical hexagonal grids, reflecting a change of navigational processing corresponding to the dimensions of the navigation corridor.…”
Section: Discussionsupporting
confidence: 69%
“…Consistently with rodent data 63 , it has recently been demonstrated that physical restrictions of navigation possibilities in the environment (e.g. by physical spatial constraints) disrupt the hexadirectional GCLR modulation in humans 64 . By such restrictions, firing fields of grid cells do not tile in typical hexagonal grids, reflecting a change of navigational processing corresponding to the dimensions of the navigation corridor.…”
Section: Discussionsupporting
confidence: 69%
“…This effect of the environment layout on spatial ability echoes recent studies showing that environmental barriers (e.g. streets) compartmentalize humans' cognitive map, disrupting the way spatial information is encoded in the entorhinal cortex [46,47]. We quantified game level's entropy in the same way as for the cities (see Methods), which only captures a facet of level's complexity.…”
Section: Limitations and Analysis Considerationsmentioning
confidence: 54%
“…We previously showed that many implementation-level predictions of this model were borne out in existing rodent grid cell data sets (Keinath et al, 2018). Neuroimaging and neural recording data have established the existence of a grid cell network in humans with striking representational parallels to the networks observed in rodents (Doeller, Barry, & Burgess, 2010;He & Brown, 2019;Jacobs et al, 2013;Julian, Keinath, Frazzetta, & Epstein, 2018;Kunz et al, 2019), including the appearance of rescaling (Nadasdy et al, 2017). Thus, it is possible that dynamic shifts in grid phase directly mediate boundaryanchored shifts in human spatial memory.…”
Section: Experiments 3: Immersive Virtual Environment With Full Visumentioning
confidence: 98%